Proprietary Costs and the Disclosure of Information About Customers - ELLIS, JESSE A.; FEE, C. EDWARD; THOMAS, SHAWN E. (Journal of Accounting Research, 2012)
ABSTRACT In deciding how much information about their firms’ customers to disclose, managers face a trade off between the benefits of reducing information asymmetry with capital market participants and the costs of aiding competitors by revealing proprietary information. This paper investigates the determinants of managers’ choices to disclose information about their firms’ customers using a comprehensive data set of customer‐information disclosures over the period 1976–2006. We find robust evidence in support of the hypothesis that proprietary costs are an important factor in firms’ disclosure choices regarding information about large customers.